Insights in Urban Resource Management: A Comprehensive Understanding of Unexplored Patterns - Zucaro, Amalia; Maselli, Gabriella; Ulgiati, Sergio (Frontiers in Sustainable Cities, 2022)
In the last few decades, the rapid urbanisation process has led to an exponential growth of resource use, making increasingly difficult to ensure the principles of sustainability within urban systems. Similar to living organisms, cities have always required resources and energy to survive. However, technological development and population growth have consequently led to increasing urban inflows and outflows, in so deeply altering the relations of cities with the environment as a source and a sink. In a planet with limited resources, the challenge should not be to find new resources but to improve the way we use them and the lifestyles that they support, or in other words, to plan strategies to generate more value and higher quality of life with fewer inputs. It is well known that cities depend on imports of external resources; however, they also benefit from internal resources and ecosystem services. Based on this framework, an urgent effort is needed to explore crucial urban issues that have not yet been adequately investigated. A strategic resource management is needed to actually move towards sustainable cities. In particular, a special focus should be placed on to: (i) monitor and properly manage the city’s resources and energy systems within the metaphor of “urban metabolism”; (ii) define innovative approaches, actions and strategies that ensure the sustainable management of non-renewable urban resources; (iii) protect and restore urban ecosystem services as valuable renewable resources, and finally (iv) envisage participatory governance processes for the appropriate allocation of resources to the common well-being.